Step 1: Solve for \( x \)
Rewriting the given equation using base 3:
\[
27 = 3^3, \quad 9^x = (3^2)^x = 3^{2x}
\]
Thus, the equation becomes:
\[
3^{x^2} = 3^3 \times 3^{2x}
\]
Using exponent addition:
\[
3^{x^2} = 3^{(3 + 2x)}
\]
Since the bases are the same, we equate exponents:
\[
x^2 = 3 + 2x
\]
Rearrange:
\[
x^2 - 2x - 3 = 0
\]
Factorizing:
\[
(x - 3)(x + 1) = 0
\]
Thus, \( x = 3 \) or \( x = -1 \).
Step 2: Evaluate the Expression
\[
\frac{2^{x^2}}{(2^x)^2}
\]
Expanding the denominator:
\[
(2^x)^2 = 2^{2x}
\]
So, the given expression simplifies to:
\[
\frac{2^{x^2}}{2^{2x}} = 2^{x^2 - 2x}
\]
Using \( x^2 - 2x = 3 + 2x - 2x = 3 \) (from earlier calculation):
\[
2^0 = 1
\]
Conclusion:
The correct answer is 1.